Radiotherapy(R) Integration(I) Strategy for Small(S)-Cell Lung Cancer in Extensive(E) Stage (RISE) with up to 10 metastases- a study protocol of a randomized phase II trial - Łukasz Kuncman; Jacek Fijuth; Damian Tworek; Ewa Sierko; Paweł Cisek; Michał Masłowski; Maja Lisik-Habib; Magdalena Orzechowska; Katarzyna Galwas-Kliber; Adam Antczak; Izabela Chmielewska; Barbara Ziółkowska; et al. (BMC Cancer)
Abstract Background The current standard of care (SoC) for patients with extensive-disease small-cell lung cancer (ED-SCLC) is chemo-immunotherapy. The efficacy of radiotherapy (RT) for chest consolidation has been established for patients with ED-SCLC who have responded to chemotherapy. There is a lack of data on incorporating RT as chest consolidation and metastasis-directed therapy for ED-SCLC. The RISE (Radiotherapy for Extensive-Stage Small-Cell Lung Cancer) study aims to evaluate the effectiveness of different RT strategies for residual lesions for patients with ED-SCLC who receive chemo-immunotherapy. Methods A total of 165 patients with ED-SCLC will be recruited, with 55 patients assigned to each of the three study arms. Patients with stabilization or partial regression, according to the Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, during chemo-immunotherapy will be included. • Arm I will serve as the control group, comprising patients who continue SoC of programmed death-ligand 1 (PD-L1)/programmed death-1 (PD-1) immunotherapy (durvalumab or atezolizumab) following platinum-based chemo-immunotherapy. • Arm II will receive the SoC with consolidative RT to the chest area and potentially, according to palliative indications to metastatic lesions, delivered in 30 Gy in 3-Gy fractions. • Arm III will receive SoC with RT of 45 Gy in 3-Gy fractions to the chest area and stereotactic body radiotherapy (SBRT) with 24 Gy in 8-Gy fractions to the metastatic lesions. Blood samples for circulating tumor DNA (ctDNA) will be collected before RT, during each week of treatment, and at the time of disease progression. The primary endpoint is progression-free survival (PFS) based on RECIST 1.1 or patient death. 1. Secondary endpoints are OS, treatment toxicity (frequency of G3 toxicity according to CTCAE v.5.0), area of progression (primary tumor localization/new lesions), Overall response rate (ORR), and the response rate in non-irradiated lesions. Discussion The study population of patients with ED-SCLC has a poor prognosis. Dose-escalated chest RT and SBRT (for up to 10 metastases) administered with modern techniques offer the possibility to improve OS and PFS. Trial registration Clinicaltrials.gov NCT06529081 (Registered 26th Jul 2024).